PELATIHAN DAN PENDAMPINGAN PENERAPAN LOCAL MARKETING OF ORGANIC PRODUCTS (IFOAM’S GUIDE FOR SME’S) BAGI KELOMPOK PETANI ORGANIK, DESA MELUNG, KECAMATAN KEDUNGBANTENG, KABUPATEN BANYUMAS - Sumarsono Sumarsono; Untung Kumorohadi (JBIMA (Jurnal Bisnis dan Manajemen), 2013)
Training and guidance for the application of Local Marketing of Organic Product (IFOAM’s Guide For SME’s) to organic farmers in the Melung village, Banyumas regency. It’s conducted to apply marketing strategies recommended by IFOAM is a guide for small and medium enterprises in local marketing in the marketing of organic products. This activity aims to 1) increase the knowledge and ability to partner with the interpersonal contact consumers for the purpose of educating consumers and convincing consumers of the advantages and benefits of organic products, and 2) increase access to consumer potential marketing partners in collaboration with grassroots (association, communication, etc.) to visit and socialization of organic products are not directly develop the strategy of word of mouth publicity for organic products.The results of activities improve their knowledge and skills for organic farmers in the implementing effective communication strategies to target consumers. Socialization of organic products to the public increase consumer knowledge about the advantages and benefits of organic products and where to get organic produce from the village and is able to gain access of organic farmers for potential consumers.